PERANAN AUDIT INTERNAL TERHADAP PENERAPAN GOOD GOVERNMENT GOVERNANCE DI PROVINSI SUMATERA SELATAN - Susi Ardiani Sri Hartaty Ardiyan Natoen Apriliriansyah Hadi (JURNAL RISET TERAPAN AKUNTANSI, 2017)
This study aims to determine the role of internal audit on the implementation of good governance inSouth Sumatra Province. This data is obtained from questionnaires distributed to internal audit in Inspectorate of South Sumatera Province. The findings of this study indicate that the influence of each variable role of internal audit research simultaneously shows that independent variables namely Indenpendensi and Competence significantly positive effect on the application of Good Government Governance. Meanwhile, Internal Audit Program variables, Implementation of Audit Pogram and Internal Audit Report has no significant positive effect on the implementation of Good Government Governance. The results of the research show that the independent variable has a significant positive effect on the implementation of Good Government Governance. The result of the research shows that the Competence variable has a significant positive effect on the application of Good Government Governance. The result of the research shows that the variable of Internal Audit Program has a significant positive effect on the implementation of Good Government Governance. The result of the research shows that the variable of Implementation of Audit Program is not realiable so it is not included in linear regression test. So it can be said that the variable Implementation of Audit Program has no significant positive effect on the implementation of Good Government Governance. Internal Audit Report partially has a significant positive effect on the dependent variable of Good Governance implementation.